Barry Project: Firm-Level Data on Irish Industrial History - Barry, Frank (Trinity College Dublin, 2023)
The book 'Industry and Policy in Independent Ireland, 1922-1972' identifies the leading indigenous and foreign-owned manufacturing firms engaged in production in Ireland at any stage over the period from the establishment of the Irish Free State in 1922 to EEC accession in January 1973. This spreadsheet provides information on the sources from which the firm-level employment numbers cited in the text are drawn.
PUBLISHED
Keywords: Business history; History of Ireland; IRELAND